O efeito doppler de ondas eletromagnéticas a partir de sequência didática - Teixeira, José Victor Bezerra (2024)
The search for improvements in physics teaching is intrinsically challenging and exciting, often requiring professionals to have knowledge beyond physics, as in the case of this work, which addresses the Doppler-Fizeau effect in Electromagnetic waves using Digital Technologies. Information and Communication (TDIC). Especially, when viewing the work in this field, one came across the limitation in approaching this effect for mechanical waves. Therefore, the present work consists of a Didactic Sequence (SD), guided by Ausubel's Meaningful Learning Theory (TAS), focused on electromagnetic waves. In this way, active methodologies were used, enabling the student to be the protagonist of the teaching-learning process using Arduino. Therefore, the impacts that the use of TDICs contributed to learning, especially in Modern Physics, were investigated. This SD was applied to a 3rd grade high school class for 8 days in progressive stages: (i) introduction, seeking to familiarize participants with the necessary concepts and Arduino, (ii) development, including practical programming activities with Arduino and ( iii) conclusion, which consisted of the experimental application to investigate the phenomenon studied in microwaves, which culminated in a doppler frequency signal observer, reflection speed meter and automated door simulation. Therefore, this DS exposed signs of significant learning found through questionnaires, conversation circles and continuous observation, which revealed an increase in performance. Thus, the importance of making physics teaching contextualized is clear, as it was possible to verify the connection of concepts that were previously disconnected from the student's reality, being then substantially related to technological applications, promoting comprehensive training through understanding the conceptualization, experimental and attitudinal procedures when relating critically to the environment in which it is inserted.